PENGARUH SOSIALISASI PERPAJAKAN DAN PEMAHAMAN PROSEDUR PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMENUHI PAJAK PPH PASAL 21 (Studi Kasus Pada Badan Pengelola Keuangan Daerah Kota Sukabumi): accounting & finance - Neneng Yanti Andriani & Dendi Mulyadi (Ekonomedia, 2019)
This study examines the effect of tax dissemination and understanding of taxation procedures on taxpayer compliance in fulfilling PPH Article 21 taxes (a case study at the Sukabumi City Regional Financial Management Agency), the method used is the survey method research conducted to collect information by compiling information. a list of questions asked of respondents, the type of technique used, the sampling technique used in this study is census (total sampling). In the ANOVA table, it can be seen that the calculated F value is 16.158 when seen in the Sig. 0.000 <0.05, the decision is that there is an influence of the simultaneous socialization of taxation and understanding of taxation procedures on taxpayer compliance with the Sukabumi City Regional Financial Management Agency. the correlation value r = 0.738 which means that it is between the value of 0.600-0.799 which means that it has a strong relationship, the nature of the relationship is positive which means that if the Socialization of Taxation and Understanding of Taxation Procedures on Taxpayer Compliance is good or increases, then Taxpayer Compliance will also increase R2x100% = (0.738 x0.738) = 0.544x100 = 54.4% so the value of KD is the same as the value of R Square X1 and X2 contributes to Taxpayer Compliance by 54.4% the remaining 45.6% is influenced by other variables besides Tax Socialization and Understanding Tax Procedures which was not examined by the researcher. The regression equation is Y = 8.552+ 0.193+ 0.359 Stating that if the existence of Taxation Socialization and Taxation Procedure Understanding increases, the Taxpayer's Compliance Value will also increase by 0.359 points.